EVALUATION OF THE ACCURACY OF PERSONALITY JUDGMENTS BASED ON WRITTEN VERBAL PRODUCTION - Tucaković, Lana; Bjekić, Jovana; Knežević, Goran (Primenjena psihologija, 2020)
The process of personality judgment occurs in daily social interactions and represents an attempt to identify characteristics of someone else’s personality, in the way to explain past and predict future behaviors. The results of this process have implications on future decisions and actions of people. This research aimed to examine the accuracy of non-expert ratings of Extraversion and Conscientiousness based on short written texts. The sample consisted of 215 participants (Mage = 28.58, SD = 10.30; 80.5% females). The exclusion criterion was that participants were psychologists or psychology students, i.e., individuals familiar with personality research and taxonomies. Participants rated Extraversion and Conscientiousness, based on the texts written by five different individuals. Criteria used to estimate the accuracy of judgments were the agreement between self-report measures on HEXACO PI-R from people who wrote the texts and ratings from participants, as well as the agreement between multiple raters. The results showed that there was a moderate self-other agreement for Extraversion and Conscientiousness. Also, the results showed that there was a high between-raters agreement for Extraversion and Conscientiousness. This study indicates that it is possible to judge one’s personality based on written verbal production, as well that raters tend to form similar impressions about the personality from written texts.